Devil's derivatives - Dunbar, Nicholas (Boston, 2011)
A compelling narrative on what went wrong with our financial system$1 (Band who$1 (Bs to blame.From an award-winning journalist who has been covering the industry for more than a decade, The Devil$1 (Bs Derivatives charts the untold story of modern financial innovation$1 (Bhow investment banks invented new financial products, how investors across the world were wooed into buying them, how regulators were seduced by the political rewards of easy credit, and how speculators made a killing from the near-meltdown of the financial system. Author Nicholas Dunbar demystifies the revolution that briefly gave finance the same intellectual respectability as theoretical physics. He explains how bankers worldwide created a secret trillion-dollar machine that delivered cheap mortgages to the masses and riches beyond dreams to the financial innovators. Fundamental to this saga is how (3z (Bthe people who hated to lose(3y (Bwere persuaded to accept risk by (3z (Bthe people who loved to win.(3y (BWhy did people come to trust and respect arcane financial tools? Who were the bankers competing to assemble the basic components into increasingly intricate machines? How did this process achieve its own unstoppable momentum$1 (Bending in collapse, bailouts, and a public outcry against the giants of finance?Provocative and intriguing, The Devil$1 (Bs Derivatives sheds much-needed light on the forces that fueled the most brutal economic downturn since the Great Depression.s
Keywords: Derivatives securities-United states